Battery monomer and preparation method thereof, battery device and power utilization device
By dispersing carbon nanotubes on the surface of the positive electrode material of the lithium-containing phosphate battery with an olivine structure, the problem of insufficient conductivity is solved, and the battery rateability and high current cycle performance are improved.
Patent Information
- Application Number
- CN202510005881.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-15
AI Technical Summary
The positive electrode material of the lithium-containing phosphate battery with an existing olivine structure is insufficient in conductivity, which affects the battery's rateability and high current cycle performance.
By uniformly dispersing carbon nanotubes on the surface of lithium-containing phosphate, a composite positive electrode active substance is formed, its conductivity is improved, and structural stability and physical isolation are improved to a certain extent.
The conductivity of the positive electrode sheet is significantly improved, the contact resistance between the positive electrode active substances is reduced, and the rateability and high current circulation performance of the battery are improved.
Smart Images

Figure CN119833718A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery cell and a preparation method thereof, a battery device and an electrical device. Background Art
[0002] Batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. Batteries are widely used in portable electronic devices, electric vehicles and other fields.
[0003] As the application scope of batteries becomes wider and wider, the requirements for battery performance are also getting higher and higher. Summary of the invention
[0004] The present application provides a battery cell and a preparation method thereof, a battery device and an electrical device. The design method mainly improves the rate capability of the battery by increasing the conductivity of the lithium-containing phosphate with an olivine structure.
[0005] In a first aspect, the present application provides a battery cell, the battery cell comprising a positive electrode sheet and a negative electrode sheet;
[0006] The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side surface of the positive electrode current collector;
[0007] The positive electrode film layer includes a positive electrode active material;
[0008] The positive electrode active material comprises a lithium-containing phosphate with an olivine structure and carbon nanotubes, wherein the carbon nanotubes are dispersed on the surface of the lithium-containing phosphate;
[0009] The conductivity of the positive electrode active material is 3×10 -5 S / cm~9×10 -1 S / cm.
[0010] The carbon nanotubes of the present application have a one-dimensional tubular structure. The carbon nanotubes of the one-dimensional tubular structure are dispersed on the surface of the lithium-containing phosphate, and there is an intermolecular force between the two. The force enables the carbon nanotubes to be evenly dispersed on the surface of the lithium-containing phosphate without being easily agglomerated. The carbon nanotubes are mainly used as a conductive agent. The uniform dispersion of the carbon nanotubes facilitates the carbon nanotubes to exert good conductivity and also increases the conductivity of the positive active material. Specifically, the conductivity of the positive active material of the carbon nanotubes and the lithium-containing phosphate composite of the present application is 3×10 -5 S / cm~9×10 -1 S / cm, while the conductivity of lithium iron phosphate (LFP) at room temperature is 10 -9 S / cm, the conductivity of lithium iron manganese phosphate at room temperature is lower than that of lithium iron phosphate (LFP), generally around 10 -13S / cm, so the conductivity of the composite positive electrode active material of the present application is greatly improved, which further effectively reduces the contact resistance between the positive electrode active materials, improves the conductivity of the positive electrode plate, is beneficial to reduce the DC resistance of the battery, and further facilitates the high current cycle use of the battery to improve the battery's rate capability.
[0011] In some embodiments, the median particle size Dv50 of the positive electrode active material is 0.8 μm to 1.7 μm.
[0012] The median particle size of the positive electrode active material of the present application satisfies the above range, wherein the carbon nanotubes are evenly dispersed on the surface of the lithium-containing phosphate to facilitate better performance of the conductivity of the positive electrode active material.
[0013] In some embodiments, the specific surface area of the positive electrode active material is 10 m 2 / g~23m 2 / g.
[0014] When the median particle size and specific surface area of the positive electrode active material of the present application are within the above range values, on the one hand, it is convenient to better exert the conductivity of the positive electrode active material, and on the other hand, it is also convenient for the infiltration of the electrolyte. From the two aspects of electronic conductivity and ionic conductivity, it is beneficial to the high current cycle use of the battery to improve the battery's rate capability.
[0015] In some embodiments, the carbon nanotubes have an average tube length of 1 μm to 10 μm.
[0016] In some embodiments, the average diameter of the carbon nanotubes is 5 nm to 10 nm.
[0017] The carbon nanotubes of the present application have a one-dimensional tubular structure, which includes a structure in two dimensions, and therefore has a certain tube length and diameter, wherein the tube diameter of the one-dimensional tubular structure is at the nanometer level. The length of the one-dimensional tubular structure refers to the distance between one end and the other end of the tubular structure. The length of the one-dimensional tubular carbon nanotube can be measured by any method commonly used in the art, such as by photographing the carbon nanotube using a scanning electron microscope or a scanning transmission electron microscope.
[0018] In some embodiments, the present application discloses a method for determining the average tube length of carbon nanotubes in a positive electrode film layer. The specific process is as follows: the present application first places a battery cell in a 1.0 mol / L sodium hydroxide aqueous solution at room temperature for discharge treatment. After the discharge is completed, the battery cell is manually disassembled to obtain a positive electrode plate. A cryo-focused ion beam (FIB) is used to perform fine slicing of the positive electrode plate layer by layer at different thickness positions (the smallest scale can reach nanometer-level thin slices), and different layers of samples at different positions along the thickness are separated; the different layers of samples at the above different positions are placed in a scanning electron microscope, and the magnification of the equipment is adjusted to 30K / 40K. 20 to 50 carbon nanotubes are selected in the field of view, and the lengths are counted. The average value of the lengths is the average value (um) of the carbon nanotube tube lengths.
[0019] The diameter of the carbon nanotube in this application refers to the outer diameter of the carbon nanotube. As mentioned above, the carbon nanotube refers to a hollow tube structure with a diameter of at most several hundred nanometers formed by curling a single-layer or multi-layer graphene sheet according to a certain spiral angle. The measurement method of the diameter of the carbon nanotube includes any conventional method in the art, and can be measured by a similar measurement method when measuring the length of the carbon nanotube. As mentioned above, after using a cryo-focused ion beam (FIB) to obtain different layers of samples at different thickness positions of the positive electrode sheet, the different layers of samples at different positions are placed in a projection electron microscope, the magnification of the equipment is adjusted to 100K, 20 to 50 carbon nanotubes are selected in the field of view, and the diameter is counted. The average value of the diameter is the average value (nm) of the carbon nanotube diameter.
[0020] The average tube length of the carbon nanotubes of the present application is 1 μm to 10 μm, and the average tube diameter is 5 nm to 10 nm. The carbon nanotubes are evenly dispersed on the surface of the lithium phosphate, and the carbon nanotubes themselves are not easy to agglomerate, so that they can easily exert good conductivity.
[0021] In some embodiments, the mass percentage of the carbon nanotubes in the positive electrode active material is 0.1% to 1.0%.
[0022] In some embodiments, the chemical formula of the olivine-structured lithium-containing phosphate is Li a Fe x Mn y M 1-x-y P 1- m Q m O 4-n R n ;
[0023] Wherein M represents a doping element at the manganese position or the iron position, and the doping element at the manganese position or the iron position includes any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb;
[0024] Q represents a doping element at the phosphorus site, and the doping element at the phosphorus site includes any one or more of B, S, Si and N;
[0025] R represents an oxygen doping element, and the oxygen doping element includes any one or more of S, F, Cl and Br;
[0026] a is 0.9 to 1.1;
[0027] x is 0 to 1;
[0028] y is 0 to 1;
[0029] 1-xy is 0 to 0.1;
[0030] m is 0 to 0.1;
[0031] n is 0 to 0.1.
[0032] In some embodiments, the surface of the lithium-containing phosphate with an olivine structure further includes a carbon coating layer, and the carbon nanotubes are dispersed on the surface of the carbon coating layer;
[0033] The thickness of the carbon coating layer is 5nm to 20nm.
[0034] The present application forms a carbon coating layer on the surface of the lithium-containing phosphate with an olivine structure. The carbon coating layer can be partially or completely coated on the surface of the lithium-containing phosphate with an olivine structure. Since the carbon coating layer has good conductivity, it is beneficial to further improve the conductivity of the positive electrode active material. At the same time, carbon nanotubes are dispersed on the surface of the carbon coating layer. The carbon nanotubes are a one-dimensional tubular structure, and the carbon coating layer is a planar structure, which is beneficial to form a surface-line combined conductive network. The conductive network is located on the surface of the lithium-containing phosphate. On the one hand, it increases the conductivity of the positive electrode active material and effectively reduces the contact resistance between the positive electrode active materials. On the other hand, the conductive network can also improve the structural stability of the internal lithium-containing phosphate to a certain extent, and is isolated from the external electrolyte by a certain degree of physical isolation to reduce the probability of side reactions, so it is beneficial to the large current cycle use of the battery to improve the battery's rate capability.
[0035] In some embodiments, the compaction density of the positive electrode film is 2.3 g / cm 3 ~2.7g / cm 3 .
[0036] In some embodiments, the porosity of the positive electrode film layer is 15% to 35%.
[0037] The positive electrode film layer of the present application has a certain porosity. Within the value range of the porosity, it is convenient for the electrolyte to fully and effectively infiltrate the positive electrode film layer, thereby increasing the ion transfer rate.
[0038] In some embodiments, the positive electrode film layer further comprises any one or more of a point-shaped conductive agent and a surface-shaped conductive agent.
[0039] The positive electrode film layer of the present application also includes other types of conductive agents, which together with carbon nanotubes form a conductive network, which is conducive to further reducing the contact resistance between the positive electrode active materials and improving the conductivity of the positive electrode plate. The present application discloses in these embodiments that other types of conductive agents include any one or more of point-shaped conductive agents and planar conductive agents. Among them, the point-shaped conductive agent includes any one or more of graphite, carbon black, and carbon dots, and the planar conductive agent includes graphene.
[0040] In some embodiments, the positive electrode film layer further comprises carbon black, and the mass percentage content of the carbon black in the positive electrode film layer is greater than zero and less than or equal to 3.0%;
[0041] The above carbon black satisfies any one or more of the following properties;
[0042] (1) The specific surface area of the above carbon black is ≥ 60m 2 / g;
[0043] (2) The median particle size of the carbon black is Dv50≤30 μm;
[0044] (3) The powder resistivity of the carbon black is less than 0.03 Ω·cm;
[0045] (4) The oil absorption value of the above carbon black is 200ml / 100g to 300ml / 100g.
[0046] The carbon black of the present application is a point-shaped conductive agent, which together with the carbon nanotubes is beneficial to further increase the conductivity of the positive electrode active material.
[0047] In some embodiments, the battery cell further comprises an electrolyte, and the conductivity of the electrolyte at 10° C. to 30° C. is greater than 10 mS / cm.
[0048] The conductivity of the electrolyte of the present application at room temperature is greater than 10 mS / cm and less than or equal to 20 mS / cm. The electrolyte meeting this range of values is conducive to good coordination with the positive electrode active material and improving the rate capability of the battery.
[0049] In some embodiments, the electrolyte includes an organic solvent, and the organic solvent includes a linear carboxylic acid ester.
[0050] The second aspect of the present application is to provide a method for preparing the battery monomer according to the first aspect, comprising the following preparation process:
[0051] Providing olivine-structured lithium-containing phosphates;
[0052] Preparing a composite containing lithium phosphate and a metal organic framework: the metal organic framework comprises metal ions and organic ligands, and the metal ions comprise zinc ions and cobalt ions;
[0053] Preparing a positive electrode active material: calcining the above-mentioned composite to obtain a positive electrode active material;
[0054] Preparing a positive electrode sheet: dispersing a positive electrode active material in a first organic solvent to form a positive electrode slurry, and coating the positive electrode slurry on at least one side of a positive electrode current collector to form a positive electrode film layer;
[0055] Preparation of battery cells: stacking the positive electrode sheets and the negative electrode sheets to form battery cells.
[0056] In some embodiments, the calcination is performed in an inert atmosphere, the temperature is increased to 600° C. to 800° C. at a heating rate of 3° C. / min to 10° C. / min, and maintained for 2 h to 8 h.
[0057] In some embodiments, the preparation process of the above-mentioned complex is as follows:
[0058] Preparing a first complex containing lithium phosphate and metal zinc organic framework: dispersing a mixture of zinc salt and organic solvent A and lithium phosphate in organic solvent A containing organic ligands, mixing at 50° C. to 70° C., and centrifuging to obtain the first complex;
[0059] Prepare a second complex containing lithium phosphate and a metal zinc organic framework and a metal cobalt organic framework: disperse the first complex in an organic solvent B, add a mixture of cobalt salt and organic solvent B, mix well to form a mixture C, add an organic solvent B containing an organic ligand to the mixture C, mix well at room temperature, and centrifuge to obtain a second complex.
[0060] In some embodiments, the molar ratio of the zinc salt to the organic ligand is 1:(1-10).
[0061] In some embodiments, the molar ratio of the cobalt salt to the organic ligand is 1:(1-8).
[0062] In some embodiments, the organic ligand includes any one or more of 2-methylimidazole, 2-ethylimidazole, benzimidazole, and dimethylbenzene.
[0063] In some embodiments, the organic solvent A and the organic solvent B each independently comprise any one or more of N,N-dimethylformamide, ethylene glycol, ethanol and methanol.
[0064] In some embodiments, the first organic solvent includes nitrogen-methyl pyrrolidone.
[0065] A third aspect of the present application is to provide a battery device, which includes the battery cell described in the first aspect or the battery cell manufactured by the preparation method described in the second aspect.
[0066] A fourth aspect of the present application is to provide an electrical device, which includes the battery device described in the third aspect.
[0067] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0069] Figure 1 A schematic diagram of the battery structure of some embodiments of the present application;
[0070] Figure 2 This is a schematic diagram of the exploded structure of batteries in some embodiments of the present application;
[0071] Figure 3 A schematic diagram of a vehicle structure of some embodiments of the present application;
[0072] Figure 4 A schematic diagram of the structure of a battery pack according to some embodiments of the present application;
[0073] Figure 5 A schematic diagram of the structure of a secondary battery in some embodiments of the present application;
[0074] Figure 6 A schematic diagram of the structure of a positive electrode sheet of some embodiments of the present application;
[0075] Figure 7 The scanning electron microscope (SEM) images of the positive electrode sheets of some embodiments of the present application;
[0076] Figure 8 Scanning electron microscope images (SEM) of the positive electrode sheets of some comparative examples of the present application.
[0077] The reference numerals in the specific implementation manner are as follows:
[0078] 10000, vehicles;
[0079] 1000, battery; 2000, controller; 3000, motor;
[0080] 100. Battery cell;
[0081] 200, box body; 210, first part; 220, second part;
[0082] 10. Secondary battery;
[0083] 101, housing; 102, electrode assembly; 103, cover plate;
[0084] 1. Negative electrode;
[0085] 2. positive electrode sheet; 21. positive electrode current collector; 22. positive electrode film layer;
[0086] 3. Isolation film;
[0087] 4. Carbon nanotubes;
[0088] Coordinate axis x direction: the stacking direction or thickness direction of the pole piece;
[0089] Coordinate axis y direction: length direction or width direction of the pole piece. DETAILED DESCRIPTION
[0090] Hereinafter, the battery cell and its preparation method, battery device and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0091] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0092] If not otherwise specified, all embodiments and further embodiments of the present application can be combined with each other to form a new technical solution.
[0093] Unless otherwise specified, all technical features and further technical features of the present application can be combined with each other to form a new technical solution.
[0094] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0095] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0096] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0097] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.
[0098] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0099] Unless otherwise specified, the orientations or positional relationships indicated by technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.
[0100] Batteries have been widely used in various products due to their high energy density, long cycle life, safety and reliability. In recent years, as the demand for batteries as energy has increased significantly, higher requirements have been placed on battery performance, such as conductivity.
[0101] Lithium-containing phosphates with olivine structure have gradually become the main positive electrode material for electric vehicles or energy storage batteries due to their higher safety. However, this type of material still has the technical problem of unsatisfactory conductivity.
[0102] In order to improve the conductivity of lithium-containing phosphates with an olivine structure, the present application provides a battery cell and a preparation method thereof, a battery device and an electrical device.
[0103] First, the present application discloses a battery cell, which comprises a stacked positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector; the positive electrode film layer comprises a positive electrode active material, the positive electrode active material comprises an olivine-structured lithium-containing phosphate and carbon nanotubes, the carbon nanotubes are dispersed on the surface of the lithium-containing phosphate, and the conductivity of the positive electrode active material is 3×10-5 S / cm~9×10 -1 S / cm.
[0104] The carbon nanotubes of the present invention have a one-dimensional tubular structure, and the carbon nanotubes of the one-dimensional tubular structure are dispersed on the surface of the lithium-containing phosphate to form a composite positive electrode active material. Since the carbon nanotubes of the one-dimensional tubular structure have good electrical conductivity, the contact resistance between the positive electrode active materials is effectively reduced, so that the electrical conductivity of the positive electrode active material composited with the carbon nanotubes of the present invention and the lithium-containing phosphate is 3×10 -5 S / cm~9×10 -1 S / cm, while the conductivity of lithium iron phosphate (LFP) at room temperature is 10 -9 S / cm, the conductivity of lithium iron manganese phosphate at room temperature is lower than that of lithium iron phosphate (LFP), generally around 10 -13 S / cm, so the conductivity of the composite positive electrode active material of the present application is greatly improved. The composite positive electrode active material is used to prepare the positive electrode plate, which improves the conductivity of the positive electrode plate, is beneficial to reduce the DC resistance of the battery, and further is beneficial to the high current cycle use of the battery to improve the battery's rate capability.
[0105] Therefore, the single cell provided in the present application is beneficial to improving the conductivity of the entire positive electrode plate to reduce the DC resistance of the battery, thereby improving the rate capability of the battery.
[0106] Therefore, the design method provided in this application is conducive to improving user experience.
[0107] Electrode assembly
[0108] A battery cell generally includes an electrode assembly. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator, which is arranged between the negative electrode sheet and the positive electrode sheet. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through.
[0109] Battery device
[0110] The battery apparatus mentioned in the embodiments of the present application may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple battery cells, which are connected in series, in parallel or in mixed connection through a busbar component.
[0111] In some embodiments, a battery cell assembly is generally formed by arranging a plurality of battery cells.
[0112] As an example, the battery cell assembly may be a battery module, which is formed by arranging and fixing a plurality of battery cells to form an independent module. As an example, the battery module may be formed by bundling a plurality of battery cells by a cable tie.
[0113] In some embodiments, the battery device may be a battery pack, which includes a case and one or more battery cell assemblies, wherein the battery cell assemblies are accommodated in the case.
[0114] As an example, the battery cell assembly may be a battery module, and the battery cell assembly may be accommodated in the box by fixing the battery module in the box.
[0115] As an example, the battery cell assembly may also be housed in the case by directly fixing a plurality of battery cells to the case.
[0116] As an example, the box may include a first box and a second box. The first box and the second box are buckled together to form a closed space inside the box to accommodate the battery cell assembly. The closed here means covered or closed, which can be sealed or unsealed. The first box can be a top cover or a bottom plate.
[0117] As an example, the box body may include a top cover, a frame and a bottom plate. The top cover and the bottom plate are respectively connected to the frame, so that a closed space is formed inside the box body to accommodate the battery cell assembly.
[0118] In some embodiments, the box body can be used as a part of the chassis structure of the vehicle. For example, part of the box body can become at least a part of the floor of the vehicle, or part of the box body can become at least a part of the cross beam and longitudinal beam of the vehicle.
[0119] The battery cell of the present application may include an outer package. The outer package may be used to encapsulate the electrode assembly and electrolyte composed of the above-mentioned battery cell. The outer package of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and the plastic includes but is not limited to polypropylene, polybutylene terephthalate, and polybutylene succinate, etc.
[0120] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. For example, Figure 1 The secondary battery 10 is a square structure as an example.
[0121] According to some embodiments of the present application, Figure 2 , the outer packaging may include a shell 101 and a cover plate 103. Among them, the shell 101 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 101 has an opening connected to the receiving cavity, and the cover plate 103 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 102 through a winding process or a lamination process. The electrode assembly 102 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 102. The number of electrode assemblies 102 contained in the secondary battery 10 can be one or more, and those skilled in the art can select according to specific actual needs.
[0122] The electrode assembly 102 provided in the present application is applied to a secondary battery, which is beneficial to improving the performance of the secondary battery. The secondary battery can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains (such as subways, high-speed railways, trains, EMUs, etc.), ships and satellites, energy storage systems, etc., but not limited to the above-mentioned fields.
[0123] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.
[0124] Please refer to Figure 3 , Figure 3 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.
[0125] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.
[0126] Please refer to Figure 4 , Figure 4An exploded view of a battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a battery cell 100. Conventional battery cells include primary batteries or secondary batteries. The present application specifically protects secondary batteries 10. The battery cell 100 is accommodated in the housing 200. The housing 200 is used to provide a storage space for the battery cell 100. The housing 200 can adopt a variety of structures.
[0127] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.
[0128] In the battery 1000, there may be multiple battery cells 100, and the multiple battery cells 100 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 100 are both connected in series and in parallel. The multiple battery cells 100 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple battery cells 100 in series, in parallel, or in a mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple battery cells 100.
[0129] Battery Cell
[0130] The present application discloses a battery cell in some embodiments, wherein the battery cell comprises a stacked positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector; the positive electrode film layer comprises a positive electrode active material, wherein the positive electrode active material comprises an olivine-structured lithium-containing phosphate and carbon nanotubes, wherein the carbon nanotubes are dispersed on the surface of the lithium-containing phosphate, and the conductivity of the positive electrode active material is 3×10 -5 S / cm~9×10 -1 S / cm.
[0131] The positive electrode sheet, the separator and the negative electrode sheet of the present application can be wound or laminated to form a secondary battery. Figure 5 The secondary battery 10 is formed by a stacking method, and the Figure 5 It can be seen that a negative electrode sheet 1 or a positive electrode sheet 2 is placed between two adjacent separators 3, and the negative electrode sheets 1 and the positive electrode sheets 2 are alternately arranged in sequence along the stacking direction (coordinate axis x direction). The number and size of the negative electrode sheets 1 and / or the positive electrode sheets 2 can be selected according to actual conditions, and this application will not be repeated. Figure 5 Only one lamination method is illustrated in the figure, and other lamination or winding methods are within the protection scope of this application.
[0132] like Figure 6 As shown in the figure, the positive electrode sheet 2 includes a positive electrode current collector 21 and a positive electrode film layer 22 located on at least one side of the positive electrode current collector 21, wherein: Figure 6 The positive electrode film layer 22 is schematically provided on either side of the positive electrode current collector 21. The positive electrode film layer 22 may also be provided on both sides of the positive electrode current collector 21. The positive electrode film layer 22 may be formed on the surface of the positive electrode current collector 21 by any conventional method in the art, such as coating, deposition, etc.
[0133] The carbon nanotubes of the present application refer to carbon allotropes, which include one or more cylindrical layers of carbon atoms, wherein the carbon atoms are covalently bonded into a hexagonal tiling pattern (i.e., graphene sheets), which form a hollow tube structure with a diameter of up to several hundred nanometers, that is, a one-dimensional tubular material, which has good electron mobility.
[0134] The lithium-containing phosphate of the present application has an olivine structure, which is similar to other mineral structures. Its basic structural unit is a hexagonal stacking layer, and there is an anion in the middle of each hexagonal unit. At the same time, there is a space occupied by a metal ion between two hexagonal units. In the olivine structure, the metal cation is usually 4-valent or 3-valent. The lithium-containing phosphate of the present application with an olivine structure is an important positive electrode material because of its stable structure.
[0135] The lithium-containing phosphate of the present application and the carbon nanotubes include intermolecular forces, which make the carbon nanotubes dispersed on the surface of the lithium-containing phosphate. The intermolecular forces of the present application include the interaction forces between molecules, such as van der Waals forces, etc. Although these forces are weaker than the strength of the chemical bonds within the molecules, they play a key role in the physical properties of the substance.
[0136] The carbon nanotube of the present application refers to a carbon allotrope, which is a hollow tube structure with a diameter of up to several hundred nanometers formed by curling a single layer or multiple layers of graphene sheets according to a certain spiral angle, and the tube wall of the hollow tube structure includes one or more cylindrical layers of carbon atoms. The microstructure of the carbon nanotube gives it a one-dimensional quantum effect, so the carbon nanotube has good electrical conductivity. The carbon nanotube of the present application includes any one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes. The single-walled carbon nanotube of the present application refers to a single cylindrical layer of carbon atoms, and the multi-walled carbon nanotube of the present application refers to two or more layers of carbon atoms connected by intermolecular forces, or a single layer of carbon atoms wound several times around a cylindrical hollow core.
[0137] In the present application, the carbon nanotubes with a one-dimensional tubular structure are dispersed on the surface of the lithium-containing phosphate, and there is an intermolecular force between the two, which enables the carbon nanotubes to be evenly dispersed on the surface of the lithium-containing phosphate without being easily agglomerated. The carbon nanotubes are mainly used as a conductive agent. The uniform dispersion of the carbon nanotubes facilitates the carbon nanotubes to exert good conductivity and also increases the conductivity of the positive active material. Specifically, the conductivity of the positive active material of the carbon nanotubes and the lithium-containing phosphate composite of the present application is 3×10 -5 S / cm~9×10 -1 S / cm, while the conductivity of lithium iron phosphate (LFP) at room temperature is 10 -9 S / cm, the conductivity of lithium iron manganese phosphate at room temperature is lower than that of lithium iron phosphate (LFP), generally around 10 -13 S / cm, so the conductivity of the composite positive electrode active material of the present application has been greatly improved.
[0138] The conductivity of the present application is a physical parameter that describes the ease with which charge flows in a substance. In a circuit, when a current of 1 ampere (1A) passes through a cross-section of an object and a voltage of 1 volt (1V) exists, the conductivity of the object is 1 Siemens (S). The conductivity is also the reciprocal of the resistivity. The test environment for the conductivity of the positive electrode active material of the present application is room temperature, such as 10°C to 30°C. The test method includes any conventional method in the art. The measurement method selected in the present application is GB / T30835-2014.
[0139] The test process of the conductivity of the positive electrode active material in this application includes:
[0140] (1) Obtaining positive electrode active material: First, place the battery cell in a 1.0 mol / L sodium hydroxide aqueous solution at room temperature for discharge treatment. After the discharge is completed, manually disassemble to obtain the positive electrode sheet, place the positive electrode sheet in a ceramic crucible (the ratio of the mass of the positive electrode sheet to the volume of the ceramic crucible - g / mL is 1:12), place the ceramic crucible in a box-type resistance furnace, and raise the furnace temperature from room temperature to 550°C at a heating rate of 5°C / min and keep it warm for 1 hour. Take out the ceramic crucible and cool it naturally to room temperature; take out The calcined positive electrode sheet is placed in a container filled with water according to a ratio of the mass of the positive electrode sheet to the volume of water of 1:60 (g / mL). The positive electrode sheet is stirred for 30 minutes with an electric stirrer. During the stirring process, the water temperature is 50° C. and the stirring speed is 200 r / min. After stopping the stirring, the mixture in the container is sieved with a 10-20 mesh sieve. The material on the sieve is aluminum foil, and the material under the sieve is a solution containing a positive electrode active substance. The solution containing the positive electrode active substance is filtered to obtain the positive electrode active substance.
[0141] (2) Obtaining the spectrum of the positive electrode active material: scanning electron microscope (SEM) + X-ray photoelectron spectroscopy (XPS) + X-ray diffractometer (XRD);
[0142] First, place the positive electrode active material sample on the sample stage, put it into the electron microscope chamber of the electron scanning microscope, evacuate the vacuum, turn on the electron beam, and set appropriate parameters for characterization: the parameters for observing the morphology are 10kV, the aperture is 30μm, and the working distance is 5mm~6mm. The instrument automatically records the diffraction pattern obtained from the test, analyzes the diffraction pattern, and observes that the carbon nanotubes are dispersed on the surface of the active material.
[0143] Secondly, prepare the samples required for X-ray photoelectron spectroscopy, put the samples into the X-ray photoelectron spectrometer, select the X-ray source, such as Al / Ag, preheat the X-ray source, increase the current step by step, select wide scan-element qualitative analysis, narrow scan-element chemical valence analysis according to the needs, and obtain the corresponding spectrum. According to the spectrum, the elemental composition and valence of each element of the lithium-containing phosphate can be determined, and the possible chemical formula can be deduced.
[0144] Finally, according to the description in GB / T30835-2014, all the positive active material samples were passed through a standard sieve with a mesh diameter of 0.074 mm, and the through-hole samples were evenly ground with an agate mortar and added to the groove of the sample rack, pressed with a glass sheet, and smoothed; the sample rack was placed on the test platform of the X-ray diffractometer, and the starting angle of the scan was set to 10°, the ending angle was set to 90°, the step length was set to 0.013, the scanning mode was set to continuous scanning, and then the test was started, and the instrument automatically recorded the diffraction pattern obtained by the test. The peak position and intensity of the diffraction peak in the obtained diffraction pattern were compared and analyzed with the corresponding peak position and intensity of the diffraction peak in the JCPDS (01-077-0179) standard spectrum to obtain the structural information of the positive active material of the sample.
[0145] (3) Testing the conductivity of the positive electrode active material: According to the description in GB / T30835-2014, the positive electrode active material sample powder is pressed into a cylindrical sample using a tableting mold with a known tableting area, and the resistance of the cylindrical sample is tested using an electrochemical workstation. Specifically, the prepared cylindrical sample is fixed in a three-electrode mold, and an AC impedance test is performed using an electrochemical workstation. The amplitude is set to 5 mV and the frequency is set to 1000 Hz. The absolute value of the horizontal axis reading of the electrochemical workstation test result is the resistivity R, in ohms (Ω). Then, the conductivity γ (Siemens per centimeter, S / cm) is obtained according to the calculation formula: conductivity γ = h / S×R.
[0146] In the above formula, h refers to the tableting height in centimeters (cm), and S refers to the tableting die area in square centimeters (cm 2 ).
[0147] Therefore, the design method provided in the present application effectively reduces the contact resistance between the positive electrode active materials, improves the conductivity of the positive electrode plate, is beneficial to reduce the DC resistance of the battery, and further facilitates the high current cycling use of the battery to improve the battery's rate capability.
[0148] The present application discloses in these examples that the conductivity of the positive electrode active material is 3×10 -5 S / cm, 4×10 -5 S / cm, 5×10 -5 S / cm, 6×10 -5 S / cm, 7×10 -5 S / cm, 8×10 -5 S / cm, 9×10 -5 S / cm, 1×10 -4 S / cm, 2×10 -4 S / cm, 3×10 -4 S / cm, 4×10 -4 S / cm, 5×10-4 S / cm, 6×10 -4 S / cm, 7×10 -4 S / cm, 8×10 -4 S / cm, 9×10 -4 S / cm, 1×10 -3 S / cm, 2×10 -3 S / cm, 3×10 -3 S / cm, 4×10 -3 S / cm, 5×10 -3 S / cm, 6×10 -3 S / cm, 7×10 -3 S / cm, 8×10 -3 S / cm, 9×10 -3 S / cm, 1×10 -2 S / cm, 2×10 -2 S / cm, 3×10 -2 S / cm, 4×10 - 2 S / cm, 5×10 -2 S / cm, 6×10 -2 S / cm, 7×10 -2 S / cm, 8×10 -2 S / cm, S / cm, 1×10 -1 S / cm, 2×10 -1 S / cm, 3×10 -1 S / cm, 4×10 -1 S / cm, 5×10 -1 S / cm, 6×10 -1 S / cm, 7×10 -1 S / cm, 8×10 -1 S / cm, 9×10 - 1 S / cm or any of the above two ranges.
[0149] In some embodiments, the median particle size Dv50 of the positive electrode active material is 0.8 μm to 1.7 μm.
[0150] Dv50 in this application refers to the volume of particles with a diameter greater than 50%, and the volume of particles with a diameter less than 50%, which is also called the median diameter or median diameter, and is usually used to indicate the average particle size of particles. The determination method of the median diameter includes any conventional method in the art, such as the application selects to refer to the laser diffraction particle size analysis method in these embodiments, specifically refers to the standard GB / T19077-2016 to obtain a particle size distribution diagram, and then obtains it by calculation.
[0151] The median particle size of the positive electrode active material of the present application satisfies the above range, wherein the carbon nanotubes are evenly dispersed on the surface of the lithium-containing phosphate to facilitate better performance of the conductivity of the positive electrode active material.
[0152] In these embodiments, the present application discloses that the median particle size Dv50 of the positive electrode active material is any one of 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm or any one of the values satisfying any two ranges.
[0153] In some embodiments, the specific surface area of the positive electrode active material is 5 m 2 / g~23m 2 / g.
[0154] The specific surface area of this application refers to the total area per unit mass of a material, and is usually used to characterize the physical performance parameter of the size of the outer surface of a powder material particle. It includes two types: external surface area and internal surface area, and the unit is square meters per gram (m 2 / g). The specific surface area can be determined by any conventional method in the art. For example, the present application refers to GB / T19587-2004, adopts nitrogen adsorption specific surface area analysis test method, and calculates the specific surface area of the positive electrode active material by BET (Brunauer Emmett Teller) method. The test instrument can be TRISTAR II3020 specific surface area and porosity analyzer of Micromeritics, USA.
[0155] When the median particle size and specific surface area of the positive electrode active material of the present application are within the above range values, on the one hand, it is convenient to better exert the conductivity of the positive electrode active material, and on the other hand, it is also convenient for the infiltration of the electrolyte. From the two aspects of electronic conductivity and ionic conductivity, it is beneficial to the high current cycle use of the battery to improve the battery's rate capability.
[0156] The present application discloses in these examples that the specific surface area of the positive electrode active material is 5 m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m2 / g, 23m 2 / g or any of the values within the range of both.
[0157] In some embodiments, the average tube length of the carbon nanotubes is 1 μm to 10 μm;
[0158] The average diameter of the carbon nanotubes is 5 nm to 10 nm.
[0159] As described above, the carbon nanotubes of the present application have a one-dimensional tubular structure, which includes a structure in two dimensions, and therefore has a certain tube length and diameter, wherein the tube diameter of the one-dimensional tubular structure is at the nanometer level. The length of the one-dimensional tubular structure refers to the distance between one end and the other end of the tubular structure. The length of the one-dimensional tubular carbon nanotube can be measured by any method commonly used in the art, such as by photographing the carbon nanotube using a scanning electron microscope or a scanning transmission electron microscope.
[0160] In some embodiments, the present application discloses a method for determining the average tube length of carbon nanotubes in a positive electrode film layer. The specific process is as follows: the present application first places a battery cell in a 1.0 mol / L sodium hydroxide aqueous solution at room temperature for discharge treatment. After the discharge is completed, the battery cell is manually disassembled to obtain a positive electrode plate. A cryo-focused ion beam (FIB) is used to perform fine slicing of the positive electrode plate layer by layer at different thickness positions (the smallest scale can reach nanometer-level thin slices), and different layers of samples at different positions along the thickness are separated; the different layers of samples at the above different positions are placed in a scanning electron microscope, and the magnification of the equipment is adjusted to 30K / 40K. 20 to 50 carbon nanotubes are selected in the field of view, and the lengths are counted. The average value of the lengths is the average value (um) of the carbon nanotube tube lengths.
[0161] The diameter of the carbon nanotube in this application refers to the outer diameter of the carbon nanotube. As mentioned above, the carbon nanotube refers to a hollow tube structure with a diameter of at most several hundred nanometers formed by curling a single-layer or multi-layer graphene sheet according to a certain spiral angle. The measurement method of the diameter of the carbon nanotube includes any conventional method in the art, and can be measured by a similar measurement method when measuring the length of the carbon nanotube. As mentioned above, after using a cryo-focused ion beam (FIB) to obtain different layers of samples at different thickness positions of the positive electrode sheet, the different layers of samples at different positions are placed in a projection electron microscope, the magnification of the equipment is adjusted to 100K, 20 to 50 carbon nanotubes are selected in the field of view, and the diameter is counted. The average value of the diameter is the average value (nm) of the carbon nanotube diameter.
[0162] The average tube length of the carbon nanotubes of the present application is 1 μm to 10 μm, and the average tube diameter is 5 nm to 10 nm. The carbon nanotubes are evenly dispersed on the surface of the lithium phosphate, and the carbon nanotubes themselves are not easy to agglomerate, so that they can easily exert good conductivity.
[0163] The present application discloses in these embodiments that the average tube length of the carbon nanotubes is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.
[0164] The present application discloses in these embodiments that the average diameter of the carbon nanotubes is 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm.
[0165] In some embodiments, the mass percentage of the carbon nanotubes in the positive electrode active material is 0.1% to 1.0%.
[0166] The content of carbon nanotubes in the present application refers to the amount converted and generated during the actual preparation process. Since carbon nanotubes are stable in nature, the mass change is ignored.
[0167] The carbon nanotubes of the present application serve as a conductive agent for the positive electrode active material. The conductive agent is evenly dispersed on the surface of the lithium phosphate to facilitate the conductivity. On the other hand, the amount of the conductive agent also affects the conductivity. The present application selects the content of the carbon nanotubes to be controlled within the above range to further enhance the conductivity of the positive electrode active material.
[0168] In these embodiments, the present application discloses that the mass percentage content of carbon nanotubes in the above-mentioned positive electrode active material is any one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or any one of the ranges of any two.
[0169] In some embodiments, the chemical formula of the olivine-structured lithium-containing phosphate is Li a Fe x Mn y M 1-x-y P 1- m Q m O 4-n R n ;
[0170] Wherein M represents a doping element at the manganese position or the iron position, and the doping element at the manganese position or the iron position includes any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb;
[0171] Q represents a doping element at the phosphorus site, and the doping element at the phosphorus site includes any one or more of B, S, Si and N;
[0172] R represents an oxygen doping element, and the oxygen doping element includes any one or more of S, F, Cl and Br;
[0173] a is 0.9 to 1.1;
[0174] x is 0 to 1;
[0175] y is 0 to 1;
[0176] 1-xy is 0 to 0.1;
[0177] m is 0 to 0.1;
[0178] n is 0 to 0.1.
[0179] As mentioned above, the element types of lithium phosphates in the present application, and the chemical valence state of each element can be obtained by X-ray photoelectron spectroscopy (XPS) analysis, which is not described in detail in the present application. In addition, complexation and titration method, precipitation weight method, redox method, difference method, plasma emission spectrometry, etc. are also included, among which the principle of plasma emission spectrometry is as follows:
[0180] Plasma emission spectrometry is an analytical method that uses the high-temperature excitation light source generated by plasma as the excitation light source for atomic emission spectroscopy. Different elements produce different characteristic spectra, which are projected onto the grating in the spectrometer through a lens. The grating is rotated by a motor, and the transmission mechanism accurately positions the intensity of the characteristic spectral line of the element to be measured after the spectrometry at the exit slit. The photomultiplier tube converts the spectral line intensity into electric current, which is then processed and converted by the circuit and then processed by a computer to obtain the analysis results.
[0181] The lithium-containing phosphate of the present application can be purchased through commercial channels. The purchased products have their elemental composition marked. The present application can also be further tested and analyzed with the aid of the above-mentioned chemical analysis detection methods commonly used in the field.
[0182] The doping element at the manganese position or the iron position of the present application refers to a foreign element introduced into the crystal lattice of the lithium-containing phosphate to occupy the position of the manganese ion and the iron ion, which is beneficial to improve the structural stability.
[0183] The doping element at the phosphorus position of the present application refers to a foreign element introduced into the crystal lattice of the lithium-containing phosphate to occupy the position of the phosphorus ion, which is also beneficial to improving the structural stability.
[0184] In addition, the oxygen-site doping element of the present application refers to a foreign element introduced into the crystal lattice of the lithium-containing phosphate to occupy the oxygen ion position, which is also beneficial to improving the structural stability.
[0185] In these embodiments, the present application provides that a in the chemical formula is any one of 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.05, 1.1 or any one of the ranges satisfying any two of the values.
[0186] In these embodiments, the present application provides that x in the chemical formula is 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 0.999, 1 or any one of the numerical ranges between any two of the above.
[0187] In these embodiments, the present application provides that y in the chemical formula is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 0.999, 1, or any one of the numerical ranges between any two of the above.
[0188] In these embodiments, the present application provides that 1-xy in the chemical formula is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any one of the numerical ranges between any two of the above.
[0189] In these embodiments, the present application provides that m is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1, or any one of the numerical ranges between any two of the above.
[0190] In these embodiments, the present application provides that n is any one of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1, or any one of the numerical ranges between any two of the above.
[0191] In some embodiments, the present application discloses that the chemical formula of the lithium-containing phosphate with an olivine structure is LiFePO4 (lithium iron phosphate). The lithium iron phosphate, as a positive electrode active material, exhibits good electronic conductivity.
[0192] In order to further improve the conductivity of the positive electrode active material, the present application discloses in some embodiments that the chemical formula of the lithium-containing phosphate with an olivine structure is Li a Fe x M 1-x PO4 (doped lithium iron phosphate); a is 0.9 to 1.1; x is 0.001 to 0.999, and M includes any one or more of Al, Mg, and Ni as doping elements.
[0193] The present application discloses in some embodiments that the chemical formula of the lithium-containing phosphate with an olivine structure is Li a Fe x Mn y M 1-x-y PO4 (lithium manganese iron phosphate); a is 0.9 to 1.1; x is 0.001 to 0.999; y is 0.001 to 0.999; 1-xy is 0 to 0.1.
[0194] The battery performance can be further optimized by adjusting the ratio of manganese to iron in the lithium manganese iron phosphate of the present application.
[0195] In some embodiments, the surface of the lithium-containing phosphate with an olivine structure further comprises a carbon coating layer, and the carbon nanotubes are dispersed on the surface of the carbon coating layer;
[0196] The thickness of the carbon coating layer is 5nm to 20nm.
[0197] The present application forms a carbon coating layer on the surface of the lithium-containing phosphate with an olivine structure. The carbon coating layer can be partially or completely coated on the surface of the lithium-containing phosphate with an olivine structure. Since the carbon coating layer has good conductivity, it is beneficial to further improve the conductivity of the positive electrode active material. At the same time, carbon nanotubes are dispersed on the surface of the carbon coating layer. The carbon nanotubes are a one-dimensional tubular structure, and the carbon coating layer is a planar structure, which is beneficial to form a surface-line combined conductive network. The conductive network is located on the surface of the lithium-containing phosphate. On the one hand, it increases the conductivity of the positive electrode active material and effectively reduces the contact resistance between the positive electrode active materials. On the other hand, the conductive network can also improve the structural stability of the internal lithium-containing phosphate to a certain extent, and is isolated from the external electrolyte by a certain degree of physical isolation to reduce the probability of side reactions, so it is beneficial to the large current cycle use of the battery to improve the battery's rate capability.
[0198] In these embodiments, the present application discloses that the thickness of the carbon coating layer is any one of 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, and 20nm, or any one of the numerical ranges between any two of the above.
[0199] In some embodiments, the compaction density of the positive electrode film is 2.3 g / cm 3 ~2.7g / cm 3 .
[0200] The compacted density of the positive electrode film layer of the present application can be used to characterize the energy density of the material, the compacted density of the positive electrode film layer = the surface density of the positive electrode film layer / the thickness of the positive electrode film layer, the thickness of the positive electrode film layer includes the distance between the two end faces of the positive electrode film layer along the thickness direction, the surface density of the positive electrode film layer = the weight of the single-sided positive electrode film layer / the area of the single-sided positive electrode film layer, wherein the weight of the single-sided positive electrode film layer can be obtained by weighing, and the area of the single-sided positive electrode film layer can be obtained by using the area calculation formula according to the shape of the film layer.
[0201] In some embodiments, the porosity of the positive electrode film layer is 15% to 35%.
[0202] The definition of porosity in this application includes conventional definitions in the field of materials, such as using the number of pores to represent porosity, and the porosity can be measured by the following test method, or by other conventional methods in the field;
[0203] For example, the positive electrode sheet sample is finely sliced at different thickness positions by using a cryo-focused ion beam (FIB) to obtain a positive electrode film layer, and the positive electrode film layer sample after drying is cut into a square sample of about 20 mm × 20 mm, and the thickness and actual side length are measured by a digital micrometer and a vernier caliper, and its volume is calculated as V, and its weight M0 is weighed, and then the square sample is immersed in the electrolyte, and is taken out after being soaked for 2 hours at room temperature and air atmosphere, and the electrolyte liquid adsorbed on the surface is sucked off, and then its weight M is weighed. t , then the porosity of the positive electrode film satisfies the following mathematical relationship:
[0204] Porosity = (M t -M0) / ρ×V×100%;
[0205] In the above mathematical relationship, ρ is the density of the electrolyte, in g / mm 3 , V is the volume of the square sample of the positive electrode film layer, in mm 3 , weight M0 and M t The unit is g, the weight measuring instrument is a thousandth balance, and the models of the thousandth balance, digital display micrometer, and vernier caliper include but are not limited to any conventional models in the art.
[0206] The positive electrode film layer of the present application has a certain porosity. Within the value range of the porosity, it is convenient for the electrolyte to fully and effectively infiltrate the positive electrode film layer, thereby increasing the ion transfer rate.
[0207] In some embodiments, the positive electrode film layer further comprises any one or more of a point-shaped conductive agent and a surface-shaped conductive agent.
[0208] The positive electrode film layer of the present application also includes other types of conductive agents, which together with carbon nanotubes form a conductive network, which is conducive to further reducing the contact resistance between the positive electrode active materials and improving the conductivity of the positive electrode plate. The present application discloses in these embodiments that other types of conductive agents include any one or more of point-shaped conductive agents and planar conductive agents. Among them, the point-shaped conductive agent includes any one or more of graphite, carbon black, and carbon dots, and the planar conductive agent includes graphene.
[0209] In some embodiments, the positive electrode film layer further comprises carbon black, and the mass percentage content of the carbon black in the positive electrode film layer is greater than zero and less than or equal to 3.0%;
[0210] The above carbon black satisfies any one or more of the following properties;
[0211] (1) The specific surface area of the above carbon black is ≥ 60m 2 / g;
[0212] (2) The median particle size of the carbon black is Dv50≤30 μm;
[0213] (3) The powder resistivity of the carbon black is less than 0.03 Ω·cm;
[0214] (4) The oil absorption value of the above carbon black is 200ml / 100g to 300ml / 100g.
[0215] The carbon black of the present application is a point-shaped conductive agent, which together with the carbon nanotubes is beneficial to further increase the conductivity of the positive electrode active material.
[0216] As described above, the one-dimensional tubular carbon nanotubes are evenly dispersed on the surface of the lithium-containing phosphate and are not easily agglomerated, which facilitates the carbon nanotubes to exert good conductivity.
[0217] At the same time, carbon nanotubes are dispersed on the surface of the carbon coating layer. The carbon nanotubes are a one-dimensional tubular structure, and the carbon coating layer is a planar structure, which is conducive to forming a surface-line combined conductive network. The conductive network is located on the surface of the lithium phosphate to exert better conductivity.
[0218] In addition, carbon nanotubes are dispersed on the surface of the carbon coating layer. The carbon nanotubes are a one-dimensional tubular structure, and the carbon coating layer is a planar structure. Together with the point-shaped conductive agent carbon black distributed between the positive electrode active materials, a conductive network combining points, lines, and surfaces is formed. The conductive network is located on the surface of the lithium phosphate to exert better conductivity.
[0219] The carbon black content disclosed in these examples of the present application refers to the actual amount added during the preparation process, ignoring the content variation. In order to reduce the effect of the amount of carbon black on the amount of positive electrode active material, the present application selects the amount of carbon black to meet the above range.
[0220] In these embodiments, the present application discloses that the mass percentage content of carbon black in the above-mentioned positive electrode film layer is any one of 0, 0.1%, 0.5%, 1%, 2%, 3% or any one of the numerical ranges between any two of the above.
[0221] The carbon black of this application is one of the industrial products, and its main component is carbon, and contains a small amount of oxygen, hydrogen and sulfur. Due to different preparation processes, the specific surface area, powder resistivity, etc. of various carbon blacks are different. The specific surface area and median particle size of carbon black affect its dispersibility in the positive electrode film layer, the powder resistivity refers to its conductivity, and the oil absorption value is used to indicate the porosity inside the carbon black and the degree of infiltration into the electrolyte.
[0222] In some embodiments, the specific surface area of the carbon black is ≥ 60 m 2 / g.
[0223] The definition and measurement method of the specific surface area of the present application remain the same as above. The present application discloses in some embodiments that the specific surface area of carbon black is greater than or equal to 60 m 2 / g, and less than or equal to 500m 2 / g. Carbon black meeting this range is easy to disperse in the positive electrode film layer and exhibits good conductivity.
[0224] The present application discloses in these examples that the specific surface area of carbon black is 60 m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g or any of the values satisfying any two of the above ranges.
[0225] In some embodiments, the carbon black has a Dv50 ≤ 30 μm.
[0226] The Dv50 of the present application includes 50% of the volume of particles with a diameter greater than it and 50% of the volume of particles with a diameter less than it, also known as the median diameter, which is usually used to represent the average particle size of particles. In these embodiments, the present application selects to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain a particle size distribution diagram, and then obtains it by calculation.
[0227] In some embodiments, the Dv50 of carbon black is 2 μm to 30 μm. Carbon black meeting this range is convenient to disperse in the positive electrode film layer and forms a good conductive network together with other conductive agents.
[0228] In these embodiments, the present application discloses that the Dv50 of carbon black is any one of 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm or any one of the values satisfying any two ranges above.
[0229] In some embodiments, the powder resistivity of the carbon black is less than 0.03 Ω·cm.
[0230] The powder resistivity of the present application is also the volume resistivity, which refers to the resistance of the powder material per unit length and per unit area at room temperature (10°C to 30°C). The powder resistivity is determined by any conventional method in the art. The present application selects: using a powder resistivity measuring device (manufactured by Mitsubishi Chemical Analysis Technology Co., Ltd.: Lorester GP Powder Resistivity Measurement System MCP-PD-51), the sample mass is 1.2g, the powder probe unit (four-probe probe unit) uses an annular electrode, the electrode spacing is 5.0mm, the electrode radius is 1.0mm, and the sample radius is 12.5mm. The volume resistivity [Ω·cm] of the conductive powder is measured under a certain pressure (3t) with a 90V voltage limiter.
[0231] In some embodiments, the powder resistivity of carbon black is 0.001 Ω·cm to 0.02 Ω·cm. The present application selects carbon black that meets the range value, that is, uses carbon black with strong conductivity, so as to facilitate better conductivity together with the positive electrode active material.
[0232] The oil absorption value of this application refers to the volume (cm2) of dibutyl phthalate (DBP) absorbed by 100g of carbon black under specified test conditions. 3 ) number. It is used to characterize the aggregation degree of carbon black.
[0233] The measurement method of the oil absorption value of the present application includes conventional known methods in the art, specifically referring to the A method (instrumental method) specified in the national standard GB / T3780.2-2003 "Determination of the absorption value of dibutyl phthalate in carbon black part 2", and the test instrument is, for example, the oil absorption meter produced by Brabender of Germany.
[0234] The present application selects carbon black that meets the above oil absorption value range, so as to facilitate the development of good electrical conductivity, increase the liquid absorption capacity of the positive electrode plate to the electrolyte, improve the wettability of the positive electrode plate to the electrolyte, and thus facilitate the high current recycling use of the battery to improve the battery's rate capability.
[0235] In some embodiments, the battery cell further comprises an electrolyte, and the conductivity of the electrolyte at room temperature (10° C. to 30° C.) is greater than 10 mS / cm.
[0236] The conductivity of the electrolyte in this application refers to the conductivity of the electrolyte obtained by testing during the preparation of the electrolyte, and the conductivity is mainly used to reflect the ionic conductivity of the electrolyte. The conductivity of the electrolyte can be obtained by testing with a conductivity meter. For example, an appropriate amount of electrolyte can be taken, divided into 3 parts on average, and then the conductivity of each sample is measured at 25°C using a conductivity meter, and then the average value of the test results is taken as the conductivity of the electrolyte. The test instrument can be a DDS307 conductivity meter.
[0237] In some embodiments, the conductivity of the electrolyte at room temperature is greater than 10 mS / cm and less than or equal to 20 mS / cm. The electrolyte meeting this range of values is conducive to good coordination with the positive electrode active material and improving the battery's rate capability.
[0238] In some embodiments, the electrolyte includes an organic solvent including a linear carboxylic acid ester.
[0239] The linear carboxylic acid ester of the present application has good electrical conductivity at room temperature and low temperature, and together with the positive electrode plate of the present application, it is beneficial to reduce the contact resistance between the positive electrode active materials and between the positive electrode active materials and the electrolyte, which is beneficial to reduce the DC resistance of the battery, and further facilitates the high current cycle use of the battery to improve the battery's rate capability.
[0240] In some embodiments, the linear carboxylic acid ester includes one or more of ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, methyl propionate, and methyl butyrate.
[0241] The present application lists specific types of linear carboxylates in the above embodiments. The specific types of linear carboxylates are conducive to better utilizing the high current cycle use of the battery to improve the rate capability of the battery.
[0242] [Positive electrode]
[0243] According to some embodiments of the present application, as described above, the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material.
[0244] The structure and composition of the positive electrode film layer of the present application are as described above, and will not be elaborated herein.
[0245] In some embodiments of the present application, in addition to the above-mentioned positive electrode active material and conductive agent, the positive electrode film layer may or may not contain a dispersant. As mentioned above, carbon nanotubes can be evenly dispersed on the surface of lithium phosphate and are not easily agglomerated, so a dispersant for carbon nanotubes may not be used in the positive electrode film layer.
[0246] The conductive agent of the present application may include carbon black. To facilitate the dispersion of carbon black, the present application may also use a dispersant mainly used to disperse carbon black in the positive electrode film layer. The types of the dispersant include any conventional types in the art, such as cellulose and its salts, specifically including but not limited to methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and the like.
[0247] In some embodiments of the present application, the positive electrode film layer includes, in addition to the above-mentioned positive electrode active material and conductive agent, a binder, which includes but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc., or a combination of two or more thereof.
[0248] The present application discloses in some embodiments that the positive electrode current collector includes but is not limited to a metal foil or a composite current collector, the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.
[0249] The method for forming the positive electrode film layer of the present application comprises mixing the above raw materials with a solvent (such as nitrogen methyl pyrrolidone) in a certain mass ratio to form a positive electrode slurry, and evenly coating the positive electrode slurry on both sides of the positive electrode current collector; controlling a certain single-sided coating weight; and after drying, using a cold press to compact to a certain compaction density (2.3g / cm 3 ~2.7g / cm 3 ), that is, a positive electrode sheet including a positive electrode film layer is obtained.
[0250] [Method for preparing positive electrode sheet]
[0251] According to some embodiments of the present application, the preparation process of the positive electrode sheet is as follows:
[0252] Providing olivine-structured lithium-containing phosphates;
[0253] Preparing a composite containing lithium phosphate and a metal organic framework: the metal organic framework comprises metal ions and organic ligands, and the metal ions comprise zinc ions and cobalt ions;
[0254] Preparing a positive electrode active material: calcining the above-mentioned composite to obtain a positive electrode active material;
[0255] Preparing a positive electrode sheet: dispersing a positive electrode active material in a first organic solvent to form a positive electrode slurry, and coating the positive electrode slurry on at least one side of a positive electrode current collector to form a positive electrode film layer;
[0256] In some embodiments, the calcination is performed in an inert atmosphere, the temperature is increased to 600° C. to 800° C. at a heating rate of 3° C. / min to 10° C. / min, and maintained for 2 h to 8 h.
[0257] The inert atmosphere of the present application includes a rare gas atmosphere conventional in the art. The calcination of the present application is carried out in any conventional device in the art.
[0258] In these embodiments, the present application discloses a heating rate of any one of 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any one of the ranges of any two of the above.
[0259] In these embodiments, the present application discloses raising the temperature to any one of 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, and 800°C, or to any one of the values satisfying any two of the above ranges.
[0260] The present application discloses in these embodiments that the insulation time is any one of 2h, 3h, 4h, 5h, 6h, 7h, 8h or any one of the ranges of any two of the above.
[0261] In some embodiments, the preparation process of the above-mentioned complex is as follows:
[0262] Preparing a first complex containing lithium phosphate and metal zinc organic framework: dispersing a mixture of zinc salt and organic solvent A and lithium phosphate in organic solvent A containing organic ligands, mixing at 50° C. to 70° C., and centrifuging to obtain the first complex;
[0263] Prepare a second complex containing lithium phosphate and a metal zinc organic framework and a metal cobalt organic framework: disperse the first complex in an organic solvent B, add a mixture of cobalt salt and organic solvent B, mix well to form a mixture C, add an organic solvent B containing an organic ligand to the mixture C, mix well at room temperature, and centrifuge to obtain a second complex.
[0264] The present application discloses in these embodiments that in generating the first complex, the mixing temperature is any one of 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C or any one of the ranges of any two of the above.
[0265] In some embodiments, the molar ratio of the zinc salt to the organic ligand is 1:(1-10);
[0266] The molar ratio of the cobalt salt to the organic ligand is 1:(1-8);
[0267] The organic ligands include any one or more of 2-methylimidazole, 2-ethylimidazole, benzimidazole, and dimethylbenzene.
[0268] In these embodiments, the present application discloses that the molar ratio of the zinc salt to the organic ligand is any one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any one of the ranges of any two of the above.
[0269] In these embodiments, the present application discloses that the molar ratio of the cobalt salt to the organic ligand is any one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or any one of the ranges of any two of the above.
[0270] In some embodiments, the zinc salt comprises any one or more of zinc sulfate, zinc nitrate, zinc acetate, zinc chloride, or a hydrate of each zinc salt.
[0271] In some embodiments, the cobalt salt comprises any one or more of cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, or hydrates of the cobalt salts.
[0272] In some embodiments, the organic solvent A and the organic solvent B independently comprise any one or more of N,N-dimethylformamide, ethylene glycol, ethanol and methanol.
[0273] In some embodiments, in the preparation of the first complex, centrifugal separation includes centrifugation and standing, and the centrifugation method includes any conventional method in the art, and the obtained precipitate is washed with methanol or ethanol as the washing solvent, and washed 1 to 3 times.
[0274] In some embodiments, in the preparation of the first composite, drying is performed after centrifugal separation, the drying temperature is 60° C. to 120° C., and the drying time is 8 h to 24 h.
[0275] In these embodiments, the present application discloses that the drying temperature is any one of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any one of the values within the range of any two of the above.
[0276] The present application discloses in these embodiments that the drying time is any one of 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h, or any one of the ranges satisfying any two of the above.
[0277] In some embodiments, in the preparation of the second complex, centrifugal separation includes centrifugation and standing, and the centrifugation method includes any conventional method in the art, and the obtained precipitate is washed, and the washing solvent is a dichloromethane aqueous solution, such as a dichloromethane aqueous solution with a volume ratio of 1:1, and washed 1 to 3 times.
[0278] In some embodiments, in the preparation of the second composite, drying is performed after centrifugal separation, the drying temperature is 60° C. to 120° C., and the drying time is 8 h to 24 h.
[0279] In these embodiments, the present application discloses that the drying temperature is any one of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any one of the values within the range of any two of the above.
[0280] The present application discloses in these embodiments that the drying time is any one of 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h, or any one of the ranges satisfying any two of the above.
[0281] In some embodiments, the first organic solvent includes nitrogen-methyl pyrrolidone.
[0282] [Negative electrode]
[0283] The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode film layer located on one side surface or both sides surface of the negative electrode current collector. Generally speaking, the negative electrode film layer is located on both sides surface of the negative electrode current collector, and the formation method includes coating or deposition. The present application will take both sides as an example in the following.
[0284] The present application discloses in some embodiments that the compaction density of the negative electrode film layer is ≥1.65 g / cm 3 .
[0285] In the present application, the compaction density of the negative electrode film layer can be used to characterize the energy density of the material, except that the compaction density of the negative electrode film layer is used to evaluate the compaction density of the negative electrode plate as a whole. The compaction density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer includes the distance between the two end faces of the negative electrode film layer along the thickness direction. The surface density of the negative electrode film layer = the weight of the single-sided positive electrode film layer / the area of the single-sided positive electrode film layer. The weight of the single-sided positive electrode film layer can be obtained by weighing, and the area of the single-sided negative electrode film layer can be obtained by using the area calculation formula based on the shape of the film layer. The present application lists in these embodiments that the compaction density of the negative electrode film layer is ≥1.65g / cm 3 .
[0286] The present application discloses in some embodiments that the negative electrode film layer includes a negative electrode active material, and the active material includes one or more of a carbonaceous material, a silicon-based material, a silicon-carbon composite material, a tin-based material and its alloy material. The carbonaceous material in the present application includes one or more combinations of artificial graphite, natural graphite, soft carbon and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, hard carbon, etc. include materials of any form conventional in the art, and include any conventional manufacturers and models in the art. The silicon-based material in the present application includes one or two of silicon-oxygen materials or silicon-carbon materials, or silicon-carbon composites. The tin-based and its alloy materials in the present application include but are not limited to Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, etc. And the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for lithium-ion batteries or sodium-ion batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0287] The present application discloses in some embodiments that the conductive agent comprises one or more of a point-shaped conductive agent, a linear conductive agent, and a planar conductive agent, wherein the point-shaped conductive agent comprises one or more of conductive carbon black (Super P or Super S), acetylene black, conductive graphite (KS-6 or KS-15 or SFG-6 or SFG-15), and Ketjen black, the linear conductive agent comprises one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon nanofibers, and the planar conductive agent comprises but is not limited to graphene.
[0288] The present application discloses in some embodiments that the negative electrode film layer includes a binder and a dispersant, etc. The binder includes but is not limited to polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyacrylamide, sodium alginate, styrene-butadiene rubber (SBR), etc. The dispersant also includes any conventional type in the art, such as cellulose and its salts, specifically including but not limited to methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc.
[0289] The present application discloses in some embodiments that the negative electrode current collector includes but is not limited to a metal foil or a composite current collector, the metal foil may be a copper foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.
[0290] The method for forming the negative electrode film layer of the present application includes mixing the above-mentioned raw materials with a solvent (such as deionized water) in a certain mass ratio to form a negative electrode slurry, defoaming the negative electrode slurry, and then evenly coating the negative electrode slurry on both sides of the negative electrode collector; controlling the single-sided coating weight; drying, and compacting to a certain compaction density using a cold press to obtain a negative electrode sheet containing a negative electrode film layer.
[0291] [Isolation film]
[0292] Some embodiments of the present application disclose an isolation membrane. The present application has no particular limitation on the type of the isolation membrane, and any known isolation membrane with a porous structure having good chemical stability and mechanical stability can be selected.
[0293] In some embodiments, the isolation membrane includes a base material layer and a coating disposed on the surface of the base material layer; the base material of the base material layer includes one or more of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide and polyamide; the coating includes a ceramic coating (CCS) and / or a polymer coating (PCS). The base material layer has a good transmittance to lithium ions, which is beneficial to the migration of lithium ions; the surface of the base material layer is provided with a coating, and the coating can further improve the mechanical properties of the isolation membrane. Furthermore, the ceramic particles in the ceramic coating include one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2 and BaSO4. Further, the polymer material of the polymer coating includes one or more of polyethylene (PE), polypropylene (PP), polyphenylene terephthalamide (PPTA), polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI) and polyamide (PA). The polymer coating can be made of the same or different materials as the base material layer, and the thickness of the polymer coating and the base material layer can be different. Further, the thickness of the polymer coating is equal to the thickness of the base material layer.
[0294] In other embodiments, the material of the isolation membrane is further selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0295] [Electrolyte]
[0296] In some embodiments of the present application, an electrolyte is disclosed. The electrolyte of the present application may be in liquid, solid, or gel state. Among them, the solid state is a solid electrolyte, the liquid state is a liquid electrolyte, and the gel state is a gel electrolyte. The secondary battery of the present application uses a liquid electrolyte, that is, an electrolyte. The electrolyte contains an electrolyte salt and an organic solvent. Among them, the types of electrolyte salts include any conventional types in the art, for example, including but not limited to inorganic metal salts, such as RClO4, RAsF6, RPF6, RBF4, RSbF6, RSO3F, RN(FSO2)2, etc.; fluorine-containing organic metal salts, such as RCF3SO3, RN(FSO2)(CF3SO2), RN(CF3SO2)2, RN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, RN(CF3SO2)(C4F9S O2), RC(CF3SO2)3, RPF4(CF3)2, RPF4(C2F5)2, RPF4(CF3SO2)2, RPF4(C2F5SO2)2, RBF2(CF3)2, RBF2(C2F5)2, RBF2(CF3SO2)2, RBF2(C2F5SO2)2, etc.; and metal salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, etc. The metal and R here both contain lithium ions.
[0297] According to some embodiments of the present application, the concentration of the electrolyte salt in the electrolyte is 0.1mol / L to 4mol / L. The present application discloses in these embodiments that the concentration of the electrolyte salt is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2mol / L, 2.2mol / L, 2.5mol / L, 2.8mol / L, 3mol / L, 3.2mol / L, 3.5mol / L, 3.8mol / L, 4mol / L, or any one of the values satisfying the above range.
[0298] As described above, the organic solvent comprises a linear carboxylic acid ester, and the linear carboxylic acid ester includes one or more of ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, methyl propionate, and methyl butyrate.
[0299] The linear carboxylic acid ester of the present application has good electrical conductivity at room temperature and low temperature, and together with the positive electrode plate of the present application, it is beneficial to reduce the contact resistance between the positive electrode active materials and between the positive electrode active materials and the electrolyte, which is beneficial to reduce the DC resistance of the battery, and further facilitates the high current cycle use of the battery to improve the battery's rate capability.
[0300] In some embodiments, the organic solvent comprises any one or more of carbonate compounds and ether compounds. Among them, the carbonate compound comprises one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), and fluoroethylene carbonate (FEC). The ether compound includes at least one of tetrahydrofuran, dimethyltetrahydrofuran, tetrahydropyran, dimethyltetrahydropyran, 1,2-dimethoxyethane, dipropylene glycol dimethyl ether, or dimethyl phthalate.
[0301] The organic solvent of the present application further comprises one or two of nitrile solvents and sulfone solvents, wherein the nitrile solvent comprises one or more of acetonitrile (AN), glutaronitrile (GLN) and adiponitrile (ADN). The sulfone solvent comprises at least one or a combination of two of sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0302] According to some embodiments of the present application, the electrolyte further comprises a film-forming stabilizer, which comprises a positive electrode film-forming stabilizer and a negative electrode film-forming stabilizer, wherein the positive electrode film-forming stabilizer comprises carbonate additives and / or sulfate additives, and the carbonate additives include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), vinyl ethylene carbonate (VEC) and dioctyl carbonate (CC). Sulfate additives include cyclic sulfonate additives and / or alkyl sulfate additives; further, cyclic sulfonate additives include one or more of 1,3-propane sultone (PS), propylene sultone (PES), and 3-fluoro-1,3-propane sultone (FPS); alkyl sulfate additives include one or more of vinyl sulfate (DTD), diethyl sulfate (DES) and dimethyl sulfate (DMS), and also include phosphates, such as tris (trimethylsilane) phosphate (TMSP). The negative electrode film-forming stabilizer includes one or more of boron lithium salts, phosphorus-containing lithium salts and sulfur-containing lithium salts; boron-containing lithium salts include one or more of lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB) and lithium bis(fluorooxalatoborate) (LiDFOB); phosphorus-containing lithium salts include one or more of lithium difluorophosphate (LiPO2F2), lithium fluorophosphate (Li2PO3F) and lithium phosphate (Li3PO4). Sulfur-containing lithium salts include one or more of lithium fluorosulfonate (LiFSO3), lithium sulfate (Li2SO4) and lithium sulfamate (LiSO3NH2).
[0303] The secondary battery of the present application will be described in detail below in conjunction with specific embodiments.
[0304] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0305] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0306] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.
[0307] Experimental materials:
[0308] 1. Lithium iron phosphate (LiFePO4), doped lithium iron phosphate (LiFe 0.95 Al 0.05PO4), carbon-coated lithium iron phosphate (carbon coating thickness is 7.5nm), lithium iron manganese phosphate (LiFe 0.9 Mn 0.1 PO4) are all commercially available;
[0309] 2. Zinc nitrate hexahydrate, zinc nitrate, cobalt nitrate hexahydrate, cobalt nitrate: commercially available;
[0310] 3. 2-Methylimidazole, benzimidazole: commercially available;
[0311] 4. Carbon black: Jiangxi Black Cat Carbon Black Co., Ltd.;
[0312] Preparation Example 1-1
[0313] A method for preparing a positive electrode active material is provided, the preparation method comprising the following preparation process:
[0314] (1) Provide lithium iron phosphate (LiFePO4, referred to as LFP, conductivity of 2.0×10 -9 S / cm(25℃):
[0315] (2) Preparation of a composite of lithium iron phosphate and zinc metal organic framework (LFP@ZIF-8): Add 0.01 mol of zinc nitrate hexahydrate and LFP powder to 200 ml of methanol solvent, and then add 0.08 mol of 2-methylimidazole to 100 ml of methanol solvent. Quickly pour the methanol containing 2-methylimidazole into the methanol containing zinc nitrate and LFP. After stirring at 60°C for 5 hours, wash with methanol 2 to 3 times, collect the precipitate and dry it at 80°C for 12 hours to obtain LFP@ZIF-8;
[0316] (3) Preparation of the second complex of lithium iron phosphate with metal zinc organic framework and metal cobalt organic framework (LFP@ZIF-8@ZIF-9): Disperse the LFP@ZIF-8 obtained in the above step in DMF (N,N-dimethylformamide) solvent, wherein the volume of DMF is 150 ml. Add 0.01 mol of cobalt nitrate hexahydrate to 100 ml of DMF solvent, and then add 0.05 mol of benzimidazole to 100 ml of DMF solvent. Add the DMF containing cobalt nitrate to the above DMF containing LFP@ZIF-8, stir at room temperature for 2 hours to form a mixed solution, then add the DMF containing benzimidazole to the above mixed solution, stir at room temperature for 12 hours, wash with dichloromethane aqueous solution 2 to 3 times, collect the precipitate and dry it at 80°C for 12 hours to obtain LFP@ZIF-8@ZIF-9;
[0317] (4) Preparation of positive electrode active material: The LFP@ZIF-8@ZIF-9 material prepared in the above steps is placed in an alumina tube furnace, heated to 650°C at a heating rate of 5°C / min, and maintained for 4 hours in an inert gas Ar gas environment to obtain a positive electrode active material, which includes carbon nanotubes, wherein the carbon nanotubes are dispersed on the surface of LiFePO4.
[0318] Preparation Example 1-2
[0319] A method for preparing a positive electrode active material is provided. The difference between the preparation method and Example 1-1 is that in steps (2) and (3), the amount of lithium iron phosphate added remains unchanged, and the amount of zinc nitrate hexahydrate and cobalt nitrate hexahydrate is increased to make each amount 2.5 times that of Preparation Example 1-1. Similarly, the amount of the corresponding organic ligand 2-methylimidazole used is also increased to 2.5 times that of Preparation Example 1-1.
[0320] In step (4), the temperature is increased to 750° C. at a heating rate of 3° C. / min and maintained for 4 h in an inert gas Ar environment. The rest is the same as in Example 1-1.
[0321] Other aspects are the same as those in Preparation Example 1-1.
[0322] Preparation Example 1-3
[0323] A method for preparing a positive electrode active material is provided. The difference between the preparation method and Example 1-1 is that in steps (2) and (3), the amount of lithium iron phosphate added remains unchanged, and the amount of zinc nitrate hexahydrate and cobalt nitrate hexahydrate is reduced to 0.8 times that of Preparation Example 1-1. Similarly, the amount of the corresponding organic ligand 2-methylimidazole used is also reduced to 0.8 times that of Preparation Example 1-1.
[0324] In step (4), the temperature is increased to 600° C. at a heating rate of 3° C. / min and maintained for 2 h in an inert gas Ar environment. The other conditions are the same as those in Example 1-1.
[0325] Other aspects are the same as those in Preparation Example 1-1.
[0326] Preparation Example 1-4
[0327] A method for preparing a positive electrode active material is provided. The difference between the preparation method and Example 1-1 is that in step (3), 0.01 mol of cobalt nitrate hexahydrate is added to 100 ml of DMF solvent, and then 0.08 mol of benzimidazole is added to 150 ml of DMF solvent.
[0328] In step (4), the temperature is increased to 600° C. at a heating rate of 10° C. / min and maintained for 8 h in an inert gas Ar environment. The other conditions are the same as those in Example 1-1.
[0329] Preparation Example 1-5
[0330] A method for preparing a positive electrode active material is provided. The difference between the preparation method and Example 1-1 is that in step (3), 0.01 mol of cobalt nitrate hexahydrate is added to 100 ml of DMF solvent, and then 0.01 mol of benzimidazole is added to 50 ml of DMF solvent.
[0331] In step (4), the temperature is increased to 650° C. at a heating rate of 5° C. / min and maintained for 3 h in an inert gas Ar environment. The rest is the same as in Example 1-1.
[0332] Preparation Example 2-1
[0333] A method for preparing a positive electrode active material is provided. The method is different from that of Example 1-1 in that, in step (1), a carbon-coated lithium iron phosphate (LiFePO4@C, referred to as LFP@C, having a conductivity of 5×10 -2 S / cm(25℃);
[0334] In step (4), the temperature is increased to 600° C. at a heating rate of 5° C. / min and maintained for 5 h in an inert gas Ar environment. The other conditions are the same as those in Example 1-1.
[0335] Preparation Example 3-1
[0336] A method for preparing a positive electrode active material is provided. The difference between the preparation method and Example 1-1 is that in step (1), doped lithium iron phosphate (LiFe 0.95 Al 0.05 PO4, referred to as LFAP, has a conductivity of 1.5×10 -3 S / cm(25℃);
[0337] In step (4), the temperature is increased to 800° C. at a heating rate of 5° C. / min and maintained for 5 h in an inert gas Ar environment. Other conditions are the same as those in Example 1-1.
[0338] Preparation Example 4-1
[0339] A method for preparing a positive electrode active material is provided. The difference between the preparation method and Example 1-1 is that in step (1), lithium manganese iron phosphate (LiFe 0.9 Mn 0.1 PO4, referred to as LFMP, has a conductivity of 1×10 -13S / cm(25℃);
[0340] In step (4), the temperature is increased to 600° C. at a heating rate of 5° C. / min and maintained for 5 h in an inert gas Ar environment. The other conditions are the same as those in Example 1-1.
[0341] The performance test method of the positive electrode active material prepared in the above preparation example is as follows:
[0342] ① Conductivity determination method: as described in GB / T30835-2014, the positive electrode active material sample powder is pressed into a cylindrical sample using a tableting mold with a known tableting area, and the resistance of the cylindrical sample is tested using an electrochemical workstation. Specifically, the prepared cylindrical sample is fixed in a three-electrode mold, and an electrochemical workstation is used to perform an AC impedance test, with the amplitude set to 5 mV and the frequency set to 1000 Hz. The absolute value of the horizontal axis reading of the electrochemical workstation test result is the resistivity R, in ohms (Ω), and then the conductivity γ (Siemens per centimeter, S / cm) is obtained according to the calculation formula: conductivity γ = h / S×R.
[0343] In the above formula, h refers to the tableting height in centimeters (cm), and S refers to the tableting die area in square centimeters (cm 2 ).
[0344] ②Method for determining the median particle size: refer to GB / T 19077-2016, obtain the volume particle size distribution curve of the positive electrode active material, and take the particle size corresponding to 50% of the cumulative volume distribution percentage as the average particle size Dv50. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK. Deionized water is used as the solvent, and the positive electrode active material is ultrasonically treated for 5 minutes before testing.
[0345] ③ Specific surface area determination method: refer to GB / T 19587-2004, use nitrogen adsorption specific surface area analysis test method to test, and use BET (Brunauer Emmett Teller) method to calculate the specific surface area of the positive electrode active material. The test instrument can be TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.
[0346] ④Method for determining the average tube length and average tube diameter of carbon nanotubes: Average tube diameter test method: 1) Instrument model: TEM transmission electron microscope; 2) Magnification of TEM transmission electron microscope: 100K; 3) Select 50 carbon tubes in the field of view and measure the diameters of 50 carbon tubes for statistics, and take the average value L1 (nm). Average tube length test method: 1) Instrument model: SEM scanning electron microscope; 2) Samples are dried at 60℃ for 4h; 3) Adjust the equipment magnification: 30K / 40K, 4) Select 50 carbon tubes in the field of view and measure the lengths of 50 carbon tubes for statistics, and take the average value L2 (um).
[0347] Table 1 Performance list of positive electrode active materials
[0348]
[0349] The data in Table 1 of this application are all measured at room temperature.
[0350] From Table 1, it can be seen that adjusting the preparation process of the positive electrode active material and the amount of raw materials used can adjust the content of carbon nanotubes in the positive electrode active material, and for the same type of lithium-containing phosphate, the more carbon nanotubes are formed on the surface, the more obvious the improvement effect on the conductivity of the positive electrode active material.
[0351] Combining Preparation Example 1-1 and Preparation Example 2-1, it can be seen that after the surface of lithium iron phosphate is coated with carbon material, the conductivity at room temperature is 5×10 -2 S / cm, and after a certain amount of carbon nanotubes are formed on its surface, its conductivity increases to 4.2×10 -1 S / cm, which shows that the carbon material coated on the surface of lithium iron phosphate works together with carbon nanotubes to improve the conductivity of the positive electrode active material.
[0352] Combining Preparation Example 1-1 and Preparation Example 3-1, it can be seen that after a certain amount of aluminum is doped into lithium iron phosphate, the conductivity at room temperature is 1.5×10 -3 S / cm, and after a certain amount of carbon nanotubes are formed on its surface, its conductivity increases to 6.4×10 -2 S / cm, which indicates that aluminum doping of lithium iron phosphate works together with carbon nanotubes to improve the conductivity of the positive electrode active material.
[0353] Combining Preparation Example 1-1 and Preparation Example 4-1, it can be seen that after a certain amount of manganese is doped into lithium iron phosphate, the conductivity at room temperature is 1.0×10 -13 S / cm, and after a certain amount of carbon nanotubes are formed on its surface, its conductivity increases to 7.3×10 -4 S / cm, which shows that after manganese doping of lithium iron phosphate, the conductivity decreases, but after a certain amount of carbon nanotubes are formed on its surface, the conductivity increases significantly.
[0354] Table 2 Performance parameters of carbon black
[0355]
[0356] Comparative Preparation Example 1
[0357] A lithium iron phosphate (LiFePO4, referred to as LFP) of Example 1-1 is provided, with a conductivity of 2.0×10 -9 S / cm(25℃)) without any treatment.
[0358] Example 1-1
[0359] A battery cell is provided. The battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked in sequence, and also comprises an electrolyte.
[0360] The preparation of the positive electrode sheet comprises the following steps:
[0361] (1) Preparing positive electrode slurry: dispersing the positive electrode active material prepared in Preparation Example 1-1 and the binder polyvinylidene fluoride in nitrogen methyl pyrrolidone to form a positive electrode slurry;
[0362] (2) Preparation of positive electrode sheet: The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil to obtain a positive electrode film layer; the contents of the components in the positive electrode film layer are shown in Table 3. The positive electrode sheet of this embodiment is scanned by electron microscope to obtain Figure 7 .
[0363] The positive electrode sheet was cut into circular sheets with a diameter of 14 mm using a cutting machine.
[0364] Provide negative electrode:
[0365] A metal lithium sheet with a thickness of 0.5 mm is cut into a circular sheet with a diameter of 15.8 mm by a sheet cutting machine.
[0366] Prepare electrolyte:
[0367] In an environment with a water content of less than 10ppm, non-aqueous organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 3:7 to obtain a solvent, lithium salt lithium hexafluorophosphate is added to the solvent to form an electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L, and 2%wtVC (vinylene carbonate), 1%wtDTD (vinyl sulfate), 1%wtFEC (fluoroethylene carbonate) and 0.5%wtTMSP (tri(trimethylsilyl) phosphate) are also added.
[0368] Separation film available:
[0369] A porous polyethylene (PE) film is used as the base material layer of the isolation membrane, the thickness of the base material layer is 7μm, a polymer coating (PCS) is formed on both sides of the base material layer, the thickness of the polymer coating (PCS) is 0.5μm, a ceramic coating (CCS) is formed on both sides of the polymer coating (PCS), the thickness of the ceramic coating (CCS) is 2μm, and the thickness of the formed isolation membrane is 12μm.
[0370] Preparation of battery cells:
[0371] The positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the corresponding assembly forms a stacked bare cell; the stacked bare cell is placed in an outer packaging shell, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a button cell 2032 battery is obtained, and the electrolyte injection volume is 100uL.
[0372] Example 1-2
[0373] A battery cell is provided. The battery cell is different from Example 1-1 in that the positive electrode active material prepared in Preparation Example 1-2 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0374] Examples 1-3
[0375] A battery cell is provided. The battery cell is different from Example 1-1 in that the positive electrode active material prepared in Preparation Example 1-3 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0376] Examples 1-4
[0377] A battery cell is provided. The battery cell is different from Example 1-1 in that the positive electrode active material prepared in Preparation Example 1-4 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0378] Examples 1-5
[0379] A battery cell is provided. The battery cell is different from Example 1-1 in that the positive electrode active material prepared in Preparation Example 1-5 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0380] Example 2-1
[0381] A battery cell is provided. The battery cell is different from Example 1-1 in that the positive electrode active material prepared in Preparation Example 2-1 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0382] Example 3-1
[0383] A battery cell is provided. The difference between the battery cell and Example 1-1 is that the positive electrode active material prepared in Preparation Example 3-1 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0384] Example 4-1
[0385] A battery cell is provided. The difference between the battery cell and Example 1-1 is that the positive electrode active material prepared in Preparation Example 4-1 is used to form a positive electrode film layer, and the rest is the same as Example 1-1.
[0386] Example 5-1 (the conductive agent also includes carbon black)
[0387] A primary battery cell is provided, which is different from Example 2-1 in that the conductive agent of the positive electrode film layer contains carbon black (X indicated in Table 2) in addition to carbon nanotubes. Specifically, in the process of preparing the positive electrode slurry, the positive electrode active material prepared in Preparation Example 1-2, the carbon black indicated in Table 2, and the binder polyvinylidene fluoride are dispersed in nitrogen methyl pyrrolidone to form the positive electrode slurry. The content of each component in the formed positive electrode film layer is shown in Table 3, and the rest is the same as Example 2-1.
[0388] Example 6-1
[0389] A primary battery cell is provided, which is different from Example 1-1 in that the electrolyte is different. In an environment where the water content is less than 10 ppm, lithium hexafluorophosphate is added to a non-aqueous organic solvent ethyl acetate to form an electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L, and 2% wt VC (vinyl carbonate), 1% wt DTD (vinyl sulfate), 1% wt FEC (fluoroethylene carbonate) and 0.5% wt TMSP (tris(trimethylsilyl) phosphate) are also added, and the rest is the same as Example 1-1.
[0390] Comparative Example 1
[0391] A battery cell is provided, which is different from Example 1-1 in that: preparing positive electrode slurry: dispersing the positive electrode active material of Comparative Preparation Example 1, the binder polyvinylidene fluoride and the conductive agent carbon black (X indicated in Table 2) in nitrogen methyl pyrrolidone to form positive electrode slurry; the rest is the same as Example 1-1.
[0392] Comparative Example 2
[0393] A battery cell is provided, which is different from that of embodiment 1-1 in that:
[0394] (1) providing a carbon nanotube dispersion: the carbon nanotube dispersion comprises carbon nanotubes (with an average tube diameter of 8 nm and an average tube length of 6.5 μm), a dispersant of hydrogenated nitrile rubber and a solvent of nitrogen methyl pyrrolidone, and the solid content of the carbon nanotube dispersion is 1%;
[0395] (2) Preparation of positive electrode slurry: The positive electrode active material of comparative preparation example 1, the binder polyvinylidene fluoride and the above-mentioned carbon nanotube dispersion are dispersed in nitrogen methyl pyrrolidone to form a positive electrode slurry; the rest is the same as Example 1-1. The positive electrode sheet of the comparative example is scanned by electron microscope to obtain Figure 8 , combined with Figure 7 , Figure 8 It can be seen that in the positive electrode sheet of the embodiment of the present application, the carbon nanotubes can be clearly seen to be uniformly attached to the surface of the lithium phosphate, while in the electron microscope field of comparative example 2, the dispersion state of the carbon nanotubes is not obvious.
[0396] The testing method of the positive electrode film layer obtained in the above embodiments and comparative examples is as follows:
[0397] ⑤Determination method of compaction density of positive electrode film:
[0398] Use a thickness gauge or a micrometer to obtain the thickness H of the positive electrode film layer;
[0399] Take the single-sided coated and cold-pressed positive electrode sheet (if it is a double-sided coated electrode sheet, the electrode film layer on one side can be wiped off first), punch it into small discs with an area of S0, weigh it, and record it as M1; then wipe off the electrode film layer of the weighed positive electrode sheet, weigh the weight of the current collector, and record it as M0. The surface density of the positive electrode film layer is D = (M1-M0) / S0.
[0400] Then the compaction density of the positive electrode film layer = the surface density D of the positive electrode film layer / the thickness H of the positive electrode film layer.
[0401] ⑥Determination method of the porosity of the positive electrode film:
[0402] The dried positive electrode film sample was cut into a square sample of about 20 mm × 20 mm, and the thickness and actual side length were measured by a digital micrometer and a vernier caliper, and the volume was calculated as V, and the weight was weighed as M0. Then, the square sample was immersed in the electrolyte of Example 1-1, and was taken out after being soaked at room temperature and air atmosphere for 2 hours, and the electrolyte liquid adsorbed on the surface was sucked off, and then the weight was weighed as M0. t , then the porosity of the positive electrode film satisfies the following mathematical relationship:
[0403] Porosity = (M t -M0) / ρ×V×100%;
[0404] In the above mathematical relationship, ρ is the density of the electrolyte, in g / mm 3 , V is the volume of the square sample of the positive electrode film layer, in mm 3 , weight M0 and M t The unit is g, the weight measuring instrument is a thousandth balance, and the models of the thousandth balance, digital display micrometer, and vernier caliper include but are not limited to any conventional models in the art.
[0405] Table 3 Performance list of positive electrode
[0406]
[0407]
[0408] Example 5-1 in Table 3 above further contains a dispersant (sodium carboxymethyl cellulose, 0.2 wt %), wherein the total mass percentage of the positive electrode active material, carbon black, the dispersant and the binder is 100%.
[0409] Comparative Example 2 in Table 3 above also includes conductive agent carbon nanotubes (0.5 wt%) and dispersant hydrogenated nitrile rubber (1.0 wt%) for dispersing the carbon nanotubes, wherein the total mass percentage of the positive electrode active material, carbon nanotubes, dispersant hydrogenated nitrile rubber and binder is 100%.
[0410] As shown in Table 3, since the content of carbon nanotubes in the positive electrode active material is relatively small, the impact on the porosity of the positive electrode film layer is relatively small.
[0411] Table 4 Performance list of electrolyte
[0412]
[0413] The performance tests of the batteries prepared in the above embodiments and preparation examples are as follows:
[0414] [Battery performance test]
[0415] ⑦ Detailed test method of battery cell DCR:
[0416] DCR corresponding to 50% SOC: At 25°C, the batteries corresponding to the embodiments and comparative examples were charged to 3.65V at a constant current of 1 / 3*C, and then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged at 1 / 3C for 1800s, and the voltage V1 was recorded. After leaving for 5 minutes, the batteries were discharged at 1C for 10s, and the voltage V2 was recorded. Then (V2-V1) / C was used to obtain the DC resistance DCR of the battery.
[0417] ⑧ Gram capacity at different rates
[0418] (1) Gram capacity corresponding to 1C: At 25°C, the batteries corresponding to the examples and comparative examples were charged at a constant current of 1 / 3*C to 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C, left for 5 min, and then discharged at 1C to 2.5V. The discharge capacity Q1 was recorded.
[0419] (2) Gram capacity corresponding to 5C: At 25°C, the batteries corresponding to the examples and comparative examples were charged at a constant current of 1 / 3*C to 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C, left for 5 min, and then discharged at 5C to 2.5V. The discharge capacity Q2 was recorded.
[0420] (3) Gram capacity corresponding to 10C: At 25°C, the batteries corresponding to the examples and comparative examples were charged at a constant current of 1 / 3*C to 3.65V, then charged at a constant voltage of 3.65V to a current of 0.05C, left for 5 min, and then discharged at 10C to 2.5V. The discharge capacity Q3 was recorded.
[0421] ⑨Capacity retention rate after 1000 cycles of battery:
[0422] (1) Capacity retention rate after 1000 cycles (1C): At 25°C, the batteries corresponding to the examples and comparative examples were charged to 3.65V at a constant current of 1 / 3*C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to 2.5V at 1C. The discharge capacity Q1 was recorded. After 1000 cycles under the above charge and discharge conditions, the discharge capacity at the 1000th cycle was Q1', and the capacity retention rate = Q1' / Q1×100%.
[0423] (2) Capacity retention rate after 1000 cycles (5C): At 25°C, the batteries corresponding to the examples and comparative examples were charged to 3.65V at a constant current of 1 / 3*C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to 2.5V at 5C. The discharge capacity Q2 was recorded. After 1000 cycles under the above charge and discharge conditions, the discharge capacity at the 1000th cycle was Q2', and the capacity retention rate = Q2' / Q2×100%.
[0424] (3) Capacity retention rate after 1000 cycles (10C): At 25°C, the batteries corresponding to the examples and comparative examples were charged to 3.65V at a constant current of 1 / 3*C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to 2.5V at 10C. The discharge capacity Q3 was recorded. After 1000 cycles under the above charge and discharge conditions, the discharge capacity at the 1000th cycle was Q3', and the capacity retention rate = Q3' / Q3×100%.
[0425] Table 5 Battery performance
[0426]
[0427] Combining Example 1-1 and Example 2-1 in Table 5, it can be seen that coating the surface of lithium iron phosphate with carbon material and continuing to form a certain amount of carbon nanotubes can significantly improve the capacity of the battery at a high rate while reducing the internal resistance of the battery.
[0428] Combining Example 1-1, Comparative Example 1 and Comparative Example 2 in Table 5, it can be seen that the present application forms carbon nanotubes on the surface of the lithium-containing phosphate, which effectively improves the conductivity of the battery and improves the capacity of the battery at a high rate.
[0429] Combining Example 1-1 and Example 6-1 in Table 5, it can be seen that the linear carboxylic acid ester of the present application has good conductivity at room temperature and low temperature, and together with the positive electrode plate of the present application, it is beneficial to reduce the contact resistance between the positive electrode active materials and between the positive electrode active materials and the electrolyte, which is beneficial to reduce the DC resistance of the battery, and further facilitates the high current cycle use of the battery to improve the battery's rate capability.
[0430] In summary, the battery cell provided in the present application mainly reduces the DC resistance of the battery by increasing the conductivity of the positive electrode active material, thereby improving the rate capability of the battery.
[0431] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A battery cell, characterized in that: Including positive electrode sheet and negative electrode sheet; The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side surface of the positive electrode current collector; The positive electrode film layer includes a positive electrode active material; The positive electrode active material includes lithium-containing phosphate with an olivine structure and carbon nanotubes, wherein the carbon nanotubes are dispersed on the surface of the lithium-containing phosphate; The conductivity of the positive electrode active material is 3×10 -5 S / cm~9×10 -1 S / cm.
2. The battery cell according to claim 1, characterized in that: The median particle size Dv50 of the positive electrode active material is 0.8 μm to 1.7 μm.
3. The battery cell according to any one of claims 1 to 2, characterized in that: The specific surface area of the positive electrode active material is 10m 2 / g~23m 2 / g.
4. The battery cell according to any one of claims 1 to 3, characterized in that: The average tube length of the carbon nanotubes is 1 μm to 10 μm; and / or; The average diameter of the carbon nanotubes is 5nm-10nm.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The mass percentage content of the carbon nanotubes in the positive electrode active material is 0.1% to 1.0%.
6. The battery cell according to any one of claims 1 to 5, characterized in that: The chemical formula of the lithium-containing phosphate of the olivine structure is Li a Fe x Mn y M 1-x-y P 1-m Q m O 4-n R n ; Wherein M represents a doping element at the manganese position or the iron position, and the doping element at the manganese position or the iron position includes any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb; Q represents a doping element at the phosphorus site, and the doping element at the phosphorus site includes any one or more of B, S, Si and N; R represents an oxygen doping element, and the oxygen doping element includes any one or more of S, F, Cl and Br; a is 0.9 to 1.1; x is 0 to 1; y is 0 to 1; 1-xy is 0 to 0.1; m is 0 to 0.1; n is 0 to 0.
1.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The surface of the lithium-containing phosphate with an olivine structure further includes a carbon coating layer, and the carbon nanotubes are dispersed on the surface of the carbon coating layer; The thickness of the carbon coating layer is 5nm to 20nm.
8. The battery cell according to any one of claims 1 to 7, characterized in that: The compaction density of the positive electrode film layer is 2.3 g / cm 3 ~2.7g / cm 3 ; and / or; The porosity of the positive electrode film layer is 15% to 35%.
9. The battery cell according to any one of claims 1 to 8, characterized in that: The positive electrode film layer further comprises any one or more of a point-shaped conductive agent and a surface-shaped conductive agent.
10. The battery cell according to any one of claims 1 to 9, characterized in that: The positive electrode film layer further comprises carbon black, and the mass percentage of the carbon black in the positive electrode film layer is greater than zero and less than or equal to 3.0%; The carbon black satisfies any one or more of the following properties; (1) The specific surface area of the carbon black is ≥60m 2 / g; (2) the median particle size of the carbon black is Dv50≤30 μm; (3) The powder resistivity of the carbon black is less than 0.03Ω·cm; (4) The oil absorption value of the carbon black is 200ml / 100g to 300ml / 100g.
11. The battery cell according to any one of claims 1 to 10, characterized in that: The battery cell further includes an electrolyte, and the conductivity of the electrolyte at 10° C. to 30° C. is greater than 10 mS / cm.
12. The battery cell according to claim 11, characterized in that: The electrolyte includes an organic solvent, and the organic solvent includes a linear carboxylic acid ester.
13. A method for preparing a battery monomer according to claim 1, characterized in that: The preparation process includes the following: Providing olivine-structured lithium-containing phosphates; Preparing a composite of lithium phosphate and a metal organic framework: the metal organic framework comprises metal ions and organic ligands, and the metal ions comprise zinc ions and cobalt ions; Preparing a positive electrode active material: calcining the composite to obtain a positive electrode active material; Preparing a positive electrode sheet: dispersing a positive electrode active material in a first organic solvent to form a positive electrode slurry, and coating the positive electrode slurry on at least one side of a positive electrode current collector to form a positive electrode film layer; Preparation of battery cells: stacking the positive electrode sheets and the negative electrode sheets to form battery cells.
14. The preparation method according to claim 13, characterized in that: The calcination is carried out in an inert atmosphere, the temperature is increased to 600° C. to 800° C. at a heating rate of 3° C. / min to 10° C. / min, and maintained for 2 h to 8 h.
15. The preparation method according to any one of claims 13 to 14, characterized in that: The preparation process of the composite is as follows: Preparing a first complex containing lithium phosphate and metal zinc organic framework: dispersing a mixture of zinc salt and organic solvent A and lithium phosphate in organic solvent A containing organic ligands, mixing at 50° C. to 70° C., and centrifuging to obtain the first complex; Prepare a second complex containing lithium phosphate and a metal zinc organic framework and a metal cobalt organic framework: disperse the first complex in an organic solvent B, add a mixture of cobalt salt and organic solvent B, mix well to form a mixture C, add an organic solvent B containing an organic ligand to the mixture C, mix well at room temperature, and centrifuge to obtain a second complex.
16. The preparation method according to any one of claims 13 to 15, characterized in that: The molar ratio of the zinc salt to the organic ligand is 1:(1-10); and / or; The molar ratio of the cobalt salt to the organic ligand is 1:(1-8); and / or; The organic ligand includes any one or more of 2-methylimidazole, 2-ethylimidazole, benzimidazole, and dimethylbenzene.
17. The preparation method according to any one of claims 13 to 16, characterized in that: The organic solvent A and the organic solvent B independently contain any one or more of N,N-dimethylformamide, ethylene glycol, ethanol and methanol.
18. A battery device, characterized in that: The invention comprises the battery cell according to any one of claims 1 to 12 or the battery cell prepared by the preparation method according to any one of claims 13 to 17.
19. An electrical device, characterized in that: A battery device comprising the battery device of claim 18.
Citation Information
Patent Citations
Multi-position co-doped lithium manganese iron phosphate composite material, preparation method and secondary battery
CN115863623A
Lithium iron phosphate composite material, preparation method thereof, positive plate and battery
CN118899425A
Cited By
Low-polarization single-crystal ternary positive electrode material prepared by independent fusion and application thereof
CN120709357A
Positive plate, preparation method thereof and lithium ion secondary battery
CN121687859A